Effective learning in the bilingual natural science Primary classroom? A case study - Mortimore, Louisa (Pirámide, 2024)
This investigation is a result of an ongoing collaboration between the Universidad Internacional de La Rioja (UNIR) and a private school for girls situated to the north east of Madrid. The purpose of the collaboration was to improve the functioning of bilingual education in primary through the implementation of Content and Integrated Learning (CLIL). At the time of writing, the project was nearing the end of its third year. Alongside the recent very rapid growth of bilingual education in Spain there has been growing concern regarding the depth of pupils’ learning in content subjects such as natural science. The present chapter attempts to document the experiences and professional developmental of a teaching team in the school’s first year of Content and Language Integrated Learning (CLIL). This took place in Madrid as part of an UNIR in-school CLIL training programme. This case study traces the methodologies used in the classroom as devised by the team and presents a compilation of the team’s work carried out over the year. Throughout the academic year, the teaching team used a range of scaffolding techniques that encouraged collaboration, active learning, autonomy and reflection, in an effort to achieve effective learning amongst the 4th year pupils in a bilingual natural science classroom. This article argues that effective learning in the bilingual natural science classroom is achievable, but may require a significant departure from textbook-based teaching methodologies predominant in many classrooms. Furthermore, considerable training, time, planning and departmental support are required.
Keywords: investigatión; learning; bilingual; science; Primary